Superwettable Biosensor for Disease Biomarker Detection - Yang, Yun Jun; Gao, Zhong Feng (Frontiers in Bioengineering and Biotechnology, 2022)
Bioinspired superwettable materials have aroused wide interests in recent years for their promising application fields from service life to industry. As one kind of emerging application, the superwettable surfaces used to fabricate biosensors for the detection of disease biomarkers, especially tumor biomarkers, have been extensively studied. In this mini review, we briefly summarized the sensing strategy for disease biomarker detection based on superwettable biosensors, including fluorescence, electrochemistry, surface-enhanced Raman scattering, and visual assays. Finally, the challenges and direction for future development of superwettable biosensors are also discussed.